Cultural encounters of ethnic identities: An ethnographic study of belonging in the urban landscape of Sarajevo - Zıvalı, Tülay (Graduate School, 2022)
Citizens identify and differentiate themselves from others by exercising distinct, social, cultural and spatial practices. In this way, they build on the physical environment and adapt their socio-cultural structure to it. Increasing migratory movement patterns over the last decades raises the emergence of the changing socio-cultural assemblage of the city. Ethnic identity is one of the significant predictors within the light of this cultural variation. Ethnic representations and bonding to places does not only depends on the current urban landscape, but also on the memory of the place and how it represents the common ethnic identity in the multicultural setting. The most obvious portrayal of these representations appears in the core of the cities: the public space. Urban public space has a manifold comprehension in the socio-spatial approach of urban planning. Its multiple role and varying function within the urban landscape makes public space essential in shaping the public sphere. From this perspective, the process of the formation of the socio-spatial tissue of a city can be observed by focusing on public space. Public space is always contested by the existence of various kinds of people and is made in the very contradictions that take place in it through interconnected -but often exclusive- intimacies and their spaces. In other words, public space is generally seen as the place where the culture of a city is being (per)formed and where socio-spatial interactions become observable. One of the most important ways to examine the ethnic structure in the city is to try to understand how ethnic communities reads the city and how they position social relations and social processes on urban public space. Due to the the meaning attributed to the physical spaces of the city (or to the city as a whole) is subjected to different readings by ethnic communities with different cultural characteristics, physical spaces cease to be inanimate entities and turn into important elements in personal and social memories. Sarajevo with its multi-ethnic character distinguishes various ethnic groups. Although, the major ethnic groups share similar values and traditions for centuries long. Therefore, the city has been faced with the paradox of diversity for a much longer timespan than most of the societies. A paradox, because ethnic diversity is a source of prosperity and strength. On the other hand, ethnic groups can possess places that they identify for themselves. And in between there is a thin line that has led to active conflict through the history of Sarajevo. This thesis is an ethnography of how the multi-ethnic city of Sarajevo perceive and experience public space and investigates on place attachment regarding ethnic diversity in the context of Sarajevo. Accordingly, the main research question is stated as following: How is place attachment manifested in the multicultural urban setting? Related sub-questions investigate in the theoretical association between ethnic heterogene societies and place attachment on the one hand, and the experience of place attachment from the perspective of experts and citizens in the context of Sarajevo. To unveil the research outcomes, a mixed-method model has been conducted and discussed in three stages, employing both quantitative as well as qualitative methods to mine the subject. This mixed-method model employs exploratory / theory-based research, descriptive / case-based research and explanatory / practice-based research stages. By the implementation of Ethnographic Content Analysis (ECA), qualitative (narrative) data has been translated into either qualitative or quantitative results to evaluate place attachment in the context of Sarajevo. In scholastic sense, the study aims to extend the discussion around the theoretical background about the status of the individual and its representation within the society. Therefore, a systematic literature review has been conducted and a reframed theoretical model of place attachment (with the focus on ethnic diversity) has been proposed through reexamining main approaches and reclassifying prominent factors derived from existing literature. Based on a mapping approach, a morphological reading has been conducted to identify the spatial characterization of the representative public spaces through the four key historical periods of the city. The key periods have been evaluated with the Star Model of Publicness. This part illustrated the impacts of political, economic and socio-cultural dynamics in the transition of representational public spaces of each era. The proposed model of place attachment and related hypotheses has been utilized by applying an explanatory sequential mixed method for online surveys and in-depth interviews and evaluated through an axial coding method to produce experts' and citizens' narratives about place attachment in Sarajevo. Places of attachment and degrees of inclusiveness has been visualized to reveal the representational public places of belonging in the city. In this way, the study explores the spatial dynamics of human behaviour according to their ethnic identity that are a part of the inhabitants' daily life and thus to unveil the attitudes of place attachment in case of Sarajevo. Moreover, the research provides knowledge about critical role of public space as ethnic representation and how it becomes a property of belonging. Both for the experts as well as the citizens a good comfort and image is essential to identify a place as 'successful'. Yet, the citizens identify historic values as significant for a place to prefer. These historic values are explained as shared Yugoslavian or religious values during the interviews. Experts think that both collective identity and personal identity plays a role in the formation of place attachment, while the citizens think that relationship with others can bridge a negative personal belonging to place. The perception and meaning to the certain experience may have common patterns within group members of a community which is preserved between generations. On contrary, in case of Sarajevo there seem to be an interruption in tranferring values from generation to generation. Nevertheless, the results implicate that the age differences of people have a larger impact on the comprehension of place attachment, rather than the ethnic identity. Thus, the research does not only stress on the physical factors of a broad historical comparison but is in a unique way associated with the contextual dynamics of the social structure. Consequently, the findings contextualize current debates concerning socio-spatial, socio-economic and political agendas in Sarajevo and the region. The research points out that these emerging contextualizations are twofold; the war-tourism in Sarajevo as stimulus for memory and the image of the city and, environmental attributes of place attachment in Sarajevo.
Etnik kimliklerin kültürel karşılaşmaları: Saraybosna kent peyzajında aidiyete ilişkin etnografik bir çalışma
Thesis(Ph.D.) -- Istanbul Technical University, Graduate School, 2022
Keywords: multiculturalism; çokkültürlülük; ethnicity; etnik yapı; Bosnia-Herzegovina; Bosna-Hersek; Sarajevo; Saraybosna